Handbook of quality integrated circuit manufacturing - Zorich, Robert (Academic Press, 1991)
Here is a comprehensive practical guide to entire wafer fabrication process from A to Z. Written by a practicing process engineer with years of experience, this book provides a thorough introduction to the complex field of IC manufacturing, including wafer area layout and design, yield optimization, just-in-time management systems, statistical quality control, fabrication equipment and its setup, and cleanroom techniques. In addition, it contains a wealth of information on common process problems: How to detect them, how to confirm them, and how to solve them. Whether you are a new enginner or technician just entering the field, a fabrication manager looking for ways to improve quality and production, or someone who would just like to know more about IC manufacturing, this is the book you're looking for. Key Features * Provides a readable, practical overview of the entire wafer fabrication process for new engineers and those just entering this complex field * Enables engineers and managers to improve production, raise quality levels, and solve problems that commonly occur in the fabrication process * Presents the latest techniques and gives special attention to Japanese IC manufacturing techniques, showing how they obtain outstanding quality.